Self-Development and the Emergence of New I-Positions: Emotions and Self-Dynamics - Branco, Angela Uchoa; Branco, Ana Luiza; Maduriera, Ana Flavia (Studia Psychologica: Theoria et praxis, 2008)
From a Dialogical Self Theory perspective, this paper focuses on the role played by life experiences that draw out strong emotions, and may engender actions that generate powerful affectladen feelings and emotions, altogether leading to the emergence of significant new I-positions that rearrange the DS. Our aim is to analyze the complexities of meaning construction processes, as affective fields change into new configurations along co-constructive processes of interpretation, meaning creation, and value constructions that guide individuals’ actions within culturally structured contexts. To provide evidence for the argument that emotions, values and selfconstruction processes are closely related to each other, we present and discuss two different cases: the story of a man with AIDS and his family, the way he deals with his disease and familial distress, such as the drug addiction condition of his older son, as well as the story of a homosexual woman whose strong Catholic values entail a psychological dilemma that ultimately leads to the emergence of a creative new I-position.